Analysis of urinary kallikrein-related peptidase 13 for monitoring bladder cancer. (17th November 2021) - Gruba, Natalia; Rachubik, Patrycja; Piwkowska, Agnieszka; Lesner, Adam
Abstract: Background: Bladder cancer (BC) is one of the 10 most common types of cancer worldwide, with approximately 550, 000 new cases each year. Early detection and appropriate diagnosis are important factors in successful treatment of the disease. Material and methods: We used specific fluorogenic substrate for the quantitative determination of urine kallikrein 13 (KLK13) activity in healthy ( n  = 15) and BC ( n  = 54) patients. The proteolytic activity in individual urine samples was determined by fluorescence measurements. Then, immunoenzymatic analyses (ELISA, Western blot) were performed to confirm the presence of KLK13 in the tested samples. Results: Urine samples from patients with G2 and G3 grade BC contained proteolytically active KLK13, as confirmed by kinetic analysis and immunochemical detection. KLK13 was not detected in the urine of patients with G1 grade BC. Discussion: Previous clinical study reveals the KLK13 significance for BC prognosis as increased KLK13 expression was highlighted in bladder tumours compared to normal adjacent tissues. Our findings correlate to the report. KLK13 activity was confirmed in BC patients with G2 and G3 stage of disease development. Conclusions: Using specific chromogenic/fluorogenic peptides could be useful for the non-invasive disease monitoring of BC progress.